Municipal Officials' Participation in Built Environment Policy Development in the United States. Issue 1 (September 2015) - Lemon, Stephenie C.; Goins, Karin Valentine; Schneider, Kristin L.; Brownson, Ross C.; Valko, Cheryl A.; Evenson, Kelly R.; Eyler, Amy A.; Heinrich, Katie M.; Litt, Jill; Lyn, Rodney; Reed, Hannah L.; Tompkins, Nancy O'Hara; et al.
Purpose: This study examined municipal officials' participation in built environment policy initiatives focused on land use design, transportation, and parks and recreation. Design: Web-based cross-sectional survey. Setting: Eighty-three municipalities with 50, 000 or more residents in eight states. Subjects: Four hundred fifty-three elected and appointed municipal officials. Measures: Outcomes included self-reported participation in land use design, transportation, and parks and recreation policy to increase physical activity. Independent variables included respondent position; perceptions of importance, barriers, and beliefs regarding physical activity and community design and layout; and physical activity partnership participation. Analysis: Multivariable logistic regression models. Results: Compared to other positions, public health officials had lower participation in land use design (78.3% vs. 29.0%), transportation (78.1% vs. 42.1%), and parks and recreation (67.1% vs. 26.3%) policy. Perceived limited staff was negatively associated with participation in each policy initiative. Perceptions of the extent to which physical activity was considered in community design and physical activity partnership participation were positively associated with participation in each. Perceived lack of collaboration was associated with less land use design and transportation policy participation, and awareness that community design affects physical activity was associated with more participation. Perceived lack of political will was associated with less parks and recreation policy participation. Conclusion: Public health officials are underrepresented in built environment policy initiatives. Improving collaborations may improve municipal officials' policy participation.